Non-syndrome multiple supernumerary teeth: literature review. - Yusof, W.Z. (1990)
Multiple supernumerary teeth without any associated systemic conditions or syndromes are not common. The author reviewed most of the cases reported in the English-language literature from 1969 to the present. It was found that there was a predilection of non-syndrome multiple supernumerary teeth to occur in the mandible. When analyzed according to specific sites for both jaws, there was a predominance of the multiple supernumerary teeth to occur in the premolar area, followed by the molar and the anterior regions respectively. The mandibular premolar region had the highest frequency of occurrence for both jaws combined.